2018
DOI: 10.1177/1359105317750253
|View full text |Cite
|
Sign up to set email alerts
|

Does need for cognitive closure explain individual differences in lung cancer screening? A brief report

Abstract: The need for cognitive closure describes the extent to which a person, faced with a decision, prefers any answer in lieu of continued uncertainty. This construct may be relevant in lung cancer screening, which can both reduce and increase uncertainty. We examined whether individual differences in need for cognitive closure are associated with Veterans’ completion of lung cancer screening using a self-administered survey ( N = 361). We also assessed whether need for cognitive closure moderates an assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In an interesting study on veterans, Lillie et al (2020) examined the association of NCC with lung cancer screening completion and was controlled with the individual-level sociodemographic (age, race, gender, smoking status, and level of education). Results suggested that NCC groups did not differ by sociodemographic factors, low and high NCC groups had statistically similar levels of education, age, and race/ethnicity.…”
Section: Influence Of Socio Demographic Variables On Need For Closurementioning
confidence: 99%
“…In an interesting study on veterans, Lillie et al (2020) examined the association of NCC with lung cancer screening completion and was controlled with the individual-level sociodemographic (age, race, gender, smoking status, and level of education). Results suggested that NCC groups did not differ by sociodemographic factors, low and high NCC groups had statistically similar levels of education, age, and race/ethnicity.…”
Section: Influence Of Socio Demographic Variables On Need For Closurementioning
confidence: 99%
“…Although initially the term was related to the individual educational level, it is has now been acknowledged as an inconsistent indicator of skill level [50] and, as such, we believe it should be captured individually. Cognitive closure, on the other hand, characterizes the extent to which a person, faced with a decision, prefers any answer in lieu of continued uncertainty [51]. Cognitive closure and anxiety have been related with more rapid and lower quality of decision-making and as such different type of information should be recommended to those patients.…”
Section: User Profilesmentioning
confidence: 99%
“…To achieve the goal of reducing lung cancer mortality, patients must continue to adhere to annual LCS and interim surveillance over many years. Some research has focused on describing and improving the initiation of screening (9)(10)(11)(12)(13)(14)(15), but there is limited research into adherence to follow-up testing (16). It remains unclear how patients make decisions about their continued engagement with screening and surveillance, the factors that influence these decisions, or the sources of information patients use.…”
Section: Introductionmentioning
confidence: 99%